Hemoglobin A1c Levels Predicts Acute Kidney Injury after Coronary Artery Bypass Surgery in Non-Diabetic Patients - Kocogulları,Cevdet Ugur (2017)
Abstract INTRODUCTION: Elevated hemoglobin A1c levels in patients with diabetes mellitus have been known as a risk factor for acute kidney injury after coronary artery bypass grafting. However, the relationship between hemoglobin A1c levels in non-diabetics and acute kidney injury is under debate. We aimed to investigate the association of preoperative hemoglobin A1c levels with acute kidney injury in non-diabetic patients undergoing isolated coronary artery bypass grafting. METHODS: 202 non-diabetic patients with normal renal function (serum creatinine <1.4 mg/dl) who underwent isolated coronary bypass were analyzed. Hemoglobin A1c level was measured at the baseline examination. Patients were separated into two groups according to preoperative Hemoglobin A1c level. Group 1 consisted of patients with preoperative HbA1c levels of < 5.6% and Group 2 consisted of patients with preoperative HbA1c levels of ≥ 5.6%. Acute kidney injury diagnosis was made by comparing baseline and postoperative serum creatinine to determine the presence of predefined significant change based on the Kidney Disease Improving Global Outcomes (KDIGO) definition. RESULTS: Acute kidney injury occurred in 19 (10.5%) patients after surgery. The incidence of acute kidney injury was 3.6% in Group 1 and 16.7% in Group 2. Elevated baseline hemoglobin A1c level was found to be associated with acute kidney injury (P=0.0001). None of the patients became hemodialysis dependent. The cut off value for acute kidney injury in our group of patients was 5.75%. CONCLUSION: Our findings suggest that, in non-diabetics, elevated preoperative hemoglobin A1c level may be associated with acute kidney injury in patients undergoing coronary artery bypass grafting. Prospective randomized studies in larger groups are needed to confirm these results.